Targeting different end uses of cassava: genotypic variations for cyanogenic potentials and pasting properties - Maziya-Dixon, B.B.; Dixon, A.; Adebowale, A. (Wiley, 2007)
Cassava flour has potential for multiple applications in the food industry. To develop cassava varieties for targeted household and industrial uses, it is necessary to evaluate the varietal and environmental variations in fresh root yield, cyanide potential and physic chemical properties A. total of 303 and 379 cassava varieties were grown at the International Institute of Tropical Agriculture research farm, Nigeria in 2000 and 2001, respectively and harvested at l2 months after planting. The genotypic variations in cyanide content as well as the genotype x year interactions on the cyanide contents were significant (P < 0.01). There were significant (P < 0.05) genotypic variations in all the pasting properties except peak time and pasting temperature in 2001. The observed wide varietal differences in pasting properties indicate that cassava genotype can be targeted for use in different food products, feed and industries. The clones were screened and characterised for food, feed and industrial applications.